Түлшээ үржүүлэн шатаах хурдан реакторын эхлэл голомтын дизайны судалгаа - C Одмаа (Scientific transaction of the National University of Mongolia. Physics, 2024)
Дэлхийн энергийн хэрэгцээ өсөхийн хэрээр түүнийг хангах тогтвортой, найдвартай, цэвэр эх үүсвэрийн нэг нь цөмийн эрчим хүч болно. Байгалийн ураныг үр дүнтэй ашиглах, цөмийн ашигласан түлшний хэмжээг багасгах, хуримтлалыг бууруулах, дахин боловсруулах үнэтэй үйлдвэрийн дутагдлыг нөхөх нэг арга нь түлшээ үржүүлэн шатаах хурдан реакторыг ашиглах юм. Ийм реакторт байгалийн эсвэл ядуурсан уран түлш ашиглах тул голомтыг критик төлөвт ажиллуулахын тулд нейтроны урсгал өндөртэй байрлалд хуваагдах изотопын агуулагдац өндөртэй түлшийг сэлгэн байрлуулах арга хэрэглэдэг. Энэхүү ажлаар цахиурт уран (U3Si2) түлштэй, шингэн натри хөргөлттэй, сэлгэн байрлуулах схемтэй, түлшээ үржүүлэн шатаах хурдан реакторын эхлэл голомтын дизайн хийж, транзиент анализ гүйцэтгэн нейтроникийн үзүүлэлтийг тодорхойлов. [English] World energy demand is increasing daily, so one of reliable, sustainable, and clean sources to satisfy this demand is nuclear energy. In particular, innovative fast reactor systems such as breed-and-burn (B&B) reactors can make effective use of natural uranium, reducing the amount of spent nuclear fuel as well as the accumulation of nuclear waste and the need for costly fuel reprocessing plants to separate the fissile isotopes from the spent nuclear fuel. In B&B reactors, since the core consists of natural and/or depleted uranium fuel, high reactivity or fresh fuel must then always be located in the high-neutron-flux region by appropriately shuffling the fuel assemblies during the core operating period in order to achieve a critical core. The study’s purposes were to design a start-up core design of Breed-and-Burn reactor with rotational fuel shuffling scheme using U3Si2 and sodium coolant and to demonstrate its performance at equilibrium state.